The reproductive cycle of the fresh water fish Labeo bata (Hamilton) (Cypriniformes: Cyprinidae) (Journal of Bio-Science, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/jbs.v21i0.22527 J. bio-sci. 21: 137-140, 2013